Aplikasi Perhitungan Angka Kredit Point Pengajuan Kenaikan Pangkat Guru pada Dinas Pendidikan dan Kebudayaan Kota Bengkulu - Sapri, Sapri (Jurnal Media Infotama, 2018)
This research is to create an Application for Calculating Credit Point Numbers for Applications for Promotion of Teacher Rank at the Bengkulu City Education and Culture Service using Visual Basic Programming Language 6. The system design uses structured data modeling, namely Entity Relationship Diagram (ERD) to describe the data model and Data Flow Diagram (DFD). ) to describe the functional model. This application can calculate credit points for applications for teacher promotion at the Bengkulu City Education and Culture Office.